The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1128/jcm.38.4.1670-1671.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Commercially Available Immunoglobulin M and Immunoglobulin G Immunochromatographic Test for Diagnosis of Melioidosis Infection

Abstract: An immunochromatographic test for the rapid determination of immunoglobulin M (IgM) and IgG antibodies to Burkholderia pseudomallei was evaluated by using sera from bacteriologically confirmed melioidosis patients and high-risk and clinically suspected patients, along with disease control groups. The sensitivities were 100 and 93% for the IgG and IgM tests, respectively, while the specificity was 95% for both assays. The test was rapid and simple to perform, with results obtained in 10 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Recent studies investigating the potential of ELISA and related strategies for the serodiagnosis of melioidosis using various antigen preparations have provided varying results generally with poor sensitivities and specificities (Ashdown et al , 1989; Cuzzubbo et al , 2000; Chenthamarakshan et al , 2001; O'Brien et al , 2004; Chua et al , 2005; Chantratita et al , 2007; Druar et al , 2008). Further, some of these studies have used crude antigens, which increases the potential for laboratory‐acquired infection and inconsistencies in their preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies investigating the potential of ELISA and related strategies for the serodiagnosis of melioidosis using various antigen preparations have provided varying results generally with poor sensitivities and specificities (Ashdown et al , 1989; Cuzzubbo et al , 2000; Chenthamarakshan et al , 2001; O'Brien et al , 2004; Chua et al , 2005; Chantratita et al , 2007; Druar et al , 2008). Further, some of these studies have used crude antigens, which increases the potential for laboratory‐acquired infection and inconsistencies in their preparation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these limitations, indirect fluorescent‐antibody assays (IFAs) (Ashdown, 1981) have been used, but require a fluorescent microscope, which may not be available in resource‐poor regions of endemicity. More recently, enzyme‐linked immunosorbent assays (ELISAs), and related serodiagnostic strategies, are becoming increasingly considered as diagnostic tools for melioidosis (Ashdown et al , 1989; Cuzzubbo et al , 2000; Chenthamarakshan et al , 2001; O'Brien et al , 2004; Chua et al , 2005; Chantratita et al , 2007; Druar et al , 2008). Many of these also use crude antigen preparations.…”
Section: Introductionmentioning
confidence: 99%
“…A geometric antibody index for IgM antibody in the sera of the melioidosis cases was significantly higher in cases compared with that of the noncase controls. In another study by some of the same authors, a rapid test for IgG and IgM was shown to have clinical utility (Cuzzubbo et al, 2000). A study with the intent of evaluating the utility of an IgG assay compared with other assays illustrates how the clinical and temporal context must be integrated for interpretation (Dharakul et al, 1997).…”
Section: Considerations and Concerns Raised By Analysis Of Other Infementioning
confidence: 99%
“…A geometric antibody index for IgM antibody in sera of melioidosis cases was significantly higher in cases compared with that of noncase controls. In another study, a rapid test for IgG and IgM was shown to have clinical utility (41). A study with the intent of evaluating the utility of an IgG assay compared with other assays illustrates how the clinical and temporal context must be integrated for interpretation (42).…”
Section: Considerations and Concerns Raised By Analysis Of Other Infementioning
confidence: 99%